Przekształcanie spółdzielni w organizację konkurencyjną- ewolucja czy rewolucja - Nogalski, Bogdan; Franas, Tomasz (Transformation of a co-operative structure into a competitive organization, 2006)
The study presents an economic process regarding transformation of a co-operative structure into a trading partnership. This process poses the form of restructuring a co-operative structure by means of change of the its legal form and indication of the conditions ensuring the efficient course of implementation of this process. The study is based on author's practical experience resulting from their participation in the processes of that type.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 256-264